Nonlinear Self-adjointness for a Generalized Fisher Equation in Cylindrical Coordinates - Gandarias, M.L.; Bruzón, M.S.; Rosa, M. (Journal of Applied Nonlinear Dynamics, 2026)
In this work we study a generalization of the well known Fisher equation in cylindrical coordinates. We determine the subclasses of these equations which are nonlinear self-adjoint. By using a general theorem on conservation laws proved by Nail Ibragimov and the symmetry generators we find conservation laws for these partial differential equations without classical Lagrangians.